2015
DOI: 10.2807/1560-7917.es.2015.20.43.30048
|View full text |Cite
|
Sign up to set email alerts
|

Cyclospora infection linked to travel to Mexico, June to September 2015

Abstract: Cyclospora cayetanensis was identified in 176 returned travellers from the Riviera Maya region of Mexico between 1 June and 22 September 2015; 79 in the United Kingdom (UK) and 97 in Canada. UK cases completed a food exposure questionnaire. This increase in reported Cyclospora cases highlights risks of gastrointestinal infections through travelling, limitations in Cyclospora surveillance and the need for improved hygiene in the production of food consumed in holiday resorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
(15 reference statements)
0
24
0
1
Order By: Relevance
“…Water is important in agriculture and food production, and irrigation may be conducted with water that is not of potable quality. Where this is done for salad items and soft fruit that are eaten without further treatment, then outbreaks can occur [73,74]. Contaminated water used for washing and food processing can also cause outbreaks.…”
Section: Settings Other Than Drinking Water and The Range Of Water-rmentioning
confidence: 99%
“…Water is important in agriculture and food production, and irrigation may be conducted with water that is not of potable quality. Where this is done for salad items and soft fruit that are eaten without further treatment, then outbreaks can occur [73,74]. Contaminated water used for washing and food processing can also cause outbreaks.…”
Section: Settings Other Than Drinking Water and The Range Of Water-rmentioning
confidence: 99%
“…Cyclosporiasis has been reported in Spain, France, Belgium, Italy, Germany, Greece, United Kingdom, Ireland, Sweden, Switzerland, The Netherlands, New Zealand, and Australia (Shlim et al, 1991;Clarke et al, 1996;Drenaggi et al, 1998;Puente et al, 2006;Bourée et al, 2006Bourée et al, , 2007Ortega et al, 2010). Outbreaks of cyclosporiasis have also been reported in travelers from Spain (Puente et al, 2006), Poland (Bednarska et al, 2015) and the United Kingdom (Nichols et al, 2015) (Table 2).…”
Section: Figure 1 Distribution Of Cyclosporiasis In Developing Regiomentioning
confidence: 94%
“…Young children, in the first five years of age, are more likely to develop clinical symptoms (Hoge et al, 1995;Madico et al, 1997;Sherchand et al 1999Sherchand et al , 2001Chacín-Bonilla et al, 2001;Bern et al, 2002). Among resident foreigners and expatriates, the disease is common (Clarke and McIntyre, 1996;Drenaggi et al, 1998;Shields et al, 2003a;Puente et al, 2006;Bourée et al, 2006Bourée et al, , 2007 and outbreaks have been reported (Shlim et al, 1991;Hoge et al, 1993;Rabold et al, 1994;Blans et al, 2005;Puente et al, 2006;Bednarska et al, 2015;Nichols, 2015) (Table 2). Among HIV-infected patients, Cyclospora is an important cause of diarrhea (Chacin-Bonilla, 2010).…”
Section: Population Susceptibilitymentioning
confidence: 99%
“…For example, in the USA and Canada, 4250 cyclosporiasis cases have been linked to consumption of raspberries, blackberries, and strawberries [1]. In the UK, 43 cases of cyclosporiasis were linked to the consumption of fresh strawberries and raspberries [4]. At the farm level, the presence of C. cayetanensis in berries is directly associated with the presence of the parasite in soil [5][6][7].…”
Section: Introductionmentioning
confidence: 99%